2012
DOI: 10.1016/j.str.2012.09.016
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the Cell Wall of Mycobacterium tuberculosis: Structure and Mechanism of L,D-Transpeptidase 2

Abstract: With multi-drug resistant cases of tuberculosis increasing globally, better antibiotic drugs and novel drug-targets are becoming an urgent need. Traditional β-lactam antibiotics that disrupt the D,D-transpeptidases are not effective against mycobacteria, in part because mycobacteria rely mostly on β-lactam insensitive L,D-transpeptidases for biosynthesis and maintenance of their peptidoglycan layer. This reliance plays a major role in drug-resistance and persistence of Mycobacterium tuberculosis (Mtb) infectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

21
212
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 94 publications
(233 citation statements)
references
References 39 publications
(65 reference statements)
21
212
0
Order By: Relevance
“…The crystal structure of Ldt Mt2 was recently reported by four independent groups (19)(20)(21)(22). These studies also report molecular interactions with the substrate and the carbapenem class of drugs and the mechanism of catalysis by Ldt Mt2 .…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations
“…The crystal structure of Ldt Mt2 was recently reported by four independent groups (19)(20)(21)(22). These studies also report molecular interactions with the substrate and the carbapenem class of drugs and the mechanism of catalysis by Ldt Mt2 .…”
Section: Discussionmentioning
confidence: 73%
“…Although ␤-lactams are rarely used for treatment of M. tuberculosis infection, recent reports demonstrate that the carbapenem subclass of ␤-lactams are effective against a range of M. tuberculosis strains (44)(45)(46). Although certain carbapenems have been demonstrated to bind to and inhibit L,D-transpeptidase activity (19,(21)(22)(23), it is not known if their M. tuberculosis growthinhibitory activity is a result of inhibition of specific or multiple transpeptidases. The in vivo study demonstrated that loss of ldt Mt1 and ldt Mt2 makes M. tuberculosis uniquely susceptible when exposed to a combination of amoxicillin-clavulanate and vancomycin.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been demonstrated that ␤-lactams interfere with peptidoglycan biosynthesis and metabolism in multiple ways and eventually results in cell death (17,19). Among ␤-lactams, carbapenems and penems are able to bind and inhibit activities of D,D-transpeptidases, L,D-transpeptidases, and D,D-carboxypeptidases (6,(20)(21)(22)(23)(24)(25)(26). This versatile property of (carba)penems to target multiple enzymes prompted the current study to test the clinical utility of commercially available (carba) penems in M. tuberculosis and M. abscessus isolates from patients.…”
Section: Discussionmentioning
confidence: 99%